Synthesis of new azobenzene dyes clubbed with thiazolidinone moiety and their applications. Issue 3 (25th February 2020) - Gaffer, Hatem E.; Althagafi, Ismail I.
Abstract : Purpose: The purpose of this paper is to synthesize some new azobenzene dyestuffs clubbed with thiazolidinone moiety and their solicitation in dyeing polyester fabrics representing their antibacterial evaluation. Design/methodology/approach: Herein, the authors report the synthesis of new thiazolidinone moiety after the coupling of diazotized 4-aminoacetophenone with resorcinol. The newly synthesized dyes were characterized by IR, elemental analysis, mass spectroscopy and proton nuclear magnetic resonance (1H NMR) spectral studies. The characteristics of dyeing of these dyestuffs were evaluated at optimum conditions. Concurrent with dyeing of polyester fabric for synthesized dyes with their antibacterial activity was estimated. Antimicrobial activity of the dyed fabrics at different concentrations was evaluated against gram-positive and gram-negative bacteria. Findings: Synthesized azobenzene dyestuffs clubbed with thiazolidinone dyes were applied on polyester fabrics. It was remarked that the modified dyes exhibited better colourfastness properties. Furthermore, the synthesized dyes revealed antimicrobial activity against gram-positive and gram-negative bacteria. Research limitations/implications: The synthesized azobenzene dyes for polyester dyeing were not bore earlier. Practical implications: The azobenzene dyes were accountable for giving improved colourfastness properties on polyester fabrics. Social implications: The synthesized azobenzene derivatives are sensibly expensive and applicable dyes accompanied with good antimicrobial and anticancer activities. Originality/value: A common process could be affording textiles of colour and antibacterial assets. The newly synthesized dyes containing thiazolidinone moieties with azobenzene coupler showed interesting disperse colourant for polyester with good antibacterial activity.